Bilateral acute retinal necrosis in premature newborn with skin, eye, and mouth infection presenting with vitreous and subretinal hemorrhage - Darakshanda Khurram; Syed M Ali; Igor Kozak (Indian Journal of Ophthalmology, 2020)
A premature newborn with systemic sepsis due to Candida albicans and parapsilosis developed skin, eye, and mouth herpetic infection. Ocular disease presented atypically with vitritis and pre and subretinal hemorrhage due to herpes simplex virus-1 confirmed fulminant bilateral acute retinal necrosis. Pars plana vitrectomy revealed necrotizing retinitis with poor visual prognosis. The baby has survived suffering from multiple morbidities which include post-hemorrhagic hydrocephalus, chronic lung disease, patent ductus arteriosus, and developmental delay.